2018
DOI: 10.1186/s12913-018-3684-7
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to the integration of mental health services into primary healthcare: a qualitative study among Ugandan primary care providers using the COM-B framework

Abstract: BackgroundUptake of clinical guideline recommendations into routine practice requires changes in attitudes and behaviors of the health care providers. The World Health Organization (WHO) has heavily invested in public health and health promotion globally by developing policy recommendations to guide clinical practice; however, clinical guidelines are often not applied. The success of the implementation of any guidelines depends on consideration of existing barriers and adequately addressing them. Therefore, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 55 publications
5
79
0
Order By: Relevance
“…It is important to measure the effectiveness of the program within its context before attempting to measure the outcome . The COM‐B framework has been used to explore the impact of education and to understand the barriers and facilitators to carrying out professional practices after training . We applied this framework as part of the secondary analysis of our observational data of the participant's behaviour at their workplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to measure the effectiveness of the program within its context before attempting to measure the outcome . The COM‐B framework has been used to explore the impact of education and to understand the barriers and facilitators to carrying out professional practices after training . We applied this framework as part of the secondary analysis of our observational data of the participant's behaviour at their workplace.…”
Section: Discussionmentioning
confidence: 99%
“…These three factors form the basis of the capability, opportunity and motivation model of behaviour (COM‐B). The COM‐B framework has been used in both primary research and systematic reviews to explore the impact of educational interventions and to understand the barriers and facilitators to carrying out professional practices after training .…”
Section: Introductionmentioning
confidence: 99%
“…Behaviour Change Techniques are the active, observable and replicable components that make up an intervention. COM-B/BCW have been used successfully for behavioural analysis and to design interventions in both health and non-health-related elds [26,[36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55], but to our knowledge, has been used in only one study of TB on contact tracing in a low-resource setting, to identify barriers and facilitators and to tailor interventions to improve contact investigation in Kampala [26]. In the qualitative arm, to understand the challenges in recognising and testing for TB in admitted children we analysed data from: i) semi-structured interviews, small-group discussions and key informant interviews with front line health workers and mid-level managers; ii) observations of TB trainings, sensitisation meetings, policy meetings, and hospital practices, and iii) desk review of guidelines, job aides and policy documents, which have been reported elsewhere [31].…”
Section: Using the Behaviour Change Wheel To Guide Intervention Designmentioning
confidence: 99%
“…The HC IIIs do not have general medical doctors but have all the other cadres of healthcare providers (15).…”
Section: Study Setting and Contextmentioning
confidence: 99%